Comparative Analysis of Digital Media Usage in Hungarian Religious Communities - Mónika Andok (Millah: Journal of Religious Studies, 2023)
The article demonstrates comparative research of the digital media usage of a particular Hungarian youth Catholic community (777 Community) and a Hungarian Krishna-Conscious Believers community. The first step is the descriptive stage which tends to focus on documenting how the investigated two groups were described or described themselves as religious communities online. After that, the intersection of online and offline religious communities’ practices and discourses will be described (highlight – rituals, community, identity, authority, and presence). How religious communities shape and renegotiate technological platforms according to their values, patterns, and the construction of their identity and presence in the public sphere will be observed. Attention should be given first to what religious Internet users do online, which will be revealed by the uses and gratifications approach. Following this, by using the Religious Social Shaping of Technology method to identify how these communities interpret and perceive these practices in relation to their broader religious and social identities. In conclusion, we can compare different value-based strategies and approaches within these two investigated religious communities.